FAKTOR YANG MEMPENGARUHI KEJADIAN KEMATIAN NEONATAL DI INDONESIA - Elyana Mafticha (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2016)
Almost 100% neonatal death was occured in Developing countries including Indonesia. Indonesia managed to reduce child mortality start from 1991 to 2012. Neonatal mortalityrate in Indonesiais still highon 19/1000 live births based on the IDHS 2007 and 2012. The objective of this research is to investigate the determinant of neonatal mortality in Indonesia. The study was a quantitative research, using the data Indonesia Demographic and Health Survey in 2012 were analyzed using retrospective cohort analysis strategy. Children born alive period 2007-2012 amounted to 12,750 inhabitants, into the sample. Analysis of data using univariable analysis in the form of a frequency distribution, such as the log-rank bivariate. The results of the data analysis are presented in tables or pictures, followed by discussion.Kaplan-Meier curves showed that neonatal mortality in Indonesia mainly occurred on the first day of life and on the early neonatal period. The results of bivariate analysis with log-rank test showed significant relationship betweenneonatal deaths in Indonesia and breastfeeding (p value: 0.000), the size of a baby's birth (p value: 0.000), frequency of ANC visits (p value: 0.001) and maternal age (p value: 0.007). The result showing that more than one factorsin Indonesia have an increased risk of neonatal mortality.